A Qualitative Research on Self-Regulation Practices of ELT Students in Reading Class - Harsya Danang Pradana; Ouda Eda Tena (Journal of Foreign Language Teaching and Learning, 2021)
This paper investigates the self-regulation practices in reading classes among students from a private university in Yogyakarta. In an era where students and their thinking process are the centers of the teaching and learning process, each student’s metacognition skills need to adjust the teaching methods used inside and outside the classroom. To that end, students must be aware of their metacognitive skills and self-regulating behaviors. The research method used in this paper was the quantitative method. The researchers used the interview and focused group discussion (FGD) method on gaining information regarding students' awareness of their metacognitive skills and self-regulation habits. The participants were students from a pre-determined private university in Yogyakarta, where the reading classes are known to be student-centered. The results showed that while the students could create strategies and reflect upon said strategies, they still lacked a critical component of self-regulation, namely the preparation phase. This discovery means that the students need to be aware of the importance of preparing to meet specific goals and self-motivation.